Genetic and Environmental Models of Circadian Disruption Link SRC-2 Function to Hepatic Pathology. (October 2016) - Fleet, Tiffany; Stashi, Erin; Zhu, Bokai; Rajapakshe, Kimal; Marcelo, Kathrina L.; Kettner, Nicole M.; Gorman, Blythe K.; Coarfa, Cristian; Fu, Loning; O'Malley, Bert W.; York, Brian
Circadian rhythmicity is a fundamental process that synchronizes behavioral cues with metabolic homeostasis. Disruption of daily cycles due to jet lag or shift work results in severe physiological consequences including advanced aging, metabolic syndrome, and even cancer. Our understanding of the molecular clock, which is regulated by intricate positive feedforward and negative feedback loops, has expanded to include an important metabolic transcriptional coregulator, Steroid Receptor Coactivator-2 (SRC-2), that regulates both the central clock of the suprachiasmatic nucleus (SCN) and peripheral clocks including the liver. We hypothesized that an environmental uncoupling of the light-dark phases, termed chronic circadian disruption (CCD), would lead to pathology similar to the genetic circadian disruption observed with loss of SRC-2 . We found that CCD and ablation of SRC-2 in mice led to a common comorbidity of metabolic syndrome also found in humans with circadian disruption, non-alcoholic fatty liver disease (NAFLD). The combination of SRC-2 –/– and CCD results in a more robust phenotype that correlates with human non-alcoholic steatohepatitis (NASH) and hepatocellular carcinoma (HCC) gene signatures. Either CCD or SRC-2 ablation produces an advanced aging phenotype leading to increased mortality consistent with other circadian mutant mouse models. Collectively, our studies demonstrate that SRC-2 provides an essential link between the behavioral activities influenced by light cues and the metabolic homeostasis maintained by the liver.